Evaluasi Kapasitas Sistem Drainase Permukiman Untuk Mitigasi Banjir di Kampung Cipicung Banyuresmi - Sulwan Permana; Alwin Andika (Jurnal Konstruksi, 2026)
Land conversion from green open space to residential areas reduces groundwater infiltration, while lack of maintenance of the drainage system leads to clogged channels. This study aims to evaluate the capacity of the residential drainage system in Cipicung Village, Banyuresmi Sub-district, to reduce flood risk using EPA SWMM 5.2. These floods not only cause economic losses but also disrupt daily activities and threaten the health and safety of residents. In this study, the method used was to process the maximum rainfall with the log person type III method and then tested with the chi-square and Smirnov-Kolmogorov methods. Furthermore, it calculates the rain intensity of the 5-year and 10-year return periods. Simulations use the EPA SWMM 5.2 application, to design drainage. The summary results of the EPA SWMM 5.2 application show that water overflow occurs. Overflow occurs in Channels 2 and 3 which have a peak overflow volume of 0.442 m3 / s with a duration of 4.52 hours and 0.340 m3 / s with a duration of 4.51 hours. So based on the results of trials by changing the dimensions of the channel, it can be concluded that Channels 2 and 3 are required to increase the dimensions of the existing cross section for the 5-year return period is 1.5 m x 1 m and in channel 3 is 1.2 m x 0.85 m. while for the 10-year return period is 1.7 m x 1 m and in channel 3 is 1.4 m x 0.85 m. The 10-year return period experienced an increase in discharge. The 10-year return period experienced an increase in planned discharge by 70%.